Wound healing procedure for Electric Cauter and Smart Klamp circumcisions - Dina Indarsita; Solihuddin Harahap; Sri Siswati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Khitan, often known as circumcision, is the act of cutting or removing all or a portion of the skin covering the front of the penis. This is a commonly performed minor surgical surgery, especially among men worldwide. Circumcision is performed medically to preserve genital health and prevent sexually transmitted illnesses. This study is an observational analysis aimed at determining the wound healing in electric cauter and smart clamp circumcision at the Super Sehat Clinic in Medan. This study's population and sample consisted of all patients registered at the Medan Super Sehat Clinic who underwent circumcision. The sample was determined by randomly selecting 60 individuals. The results demonstrated that the typical wound healing process with cauter electric circumcision occurred on days I, III, and VII. Where on the third day of circumcision with a smart clamp, regeneration is 90% and on the third day of circumcision with an electric cauter, regeneration is 80%, but on day seven, regeneration is 100%. To expedite the wound healing process, it is recommended that health providers perform circumcision using an electric chauter and smart clamp. Abstrak: Khitan atau sirkumsisi adalah tindakan memotong atau menghilangkan sebagian atau seluruh kulit penutup depan dari penis. Tindakan ini merupakan prosedur bedah minor yang paling sering dilakukan diseluruh dunia terutama pada laki-laki. Secara medis sirkumsisi dilakukan untuk menjaga kesehatan seksual dan mencegah penyakit menular seksual. Penelitian ini bersifat observasi analitik yang bertujuan untuk mengetahui bagaimana kesembuhan luka pada khitan electric cauter dan khitan smart klamp di Klinik Super Sehat Medan. Populasi dan sampel dalam penelitian ini adalah semua pasien yang melaksanakan khitan dan terdaftar di Klinik Super Sehat Medan sampel ditetapkan dengan cara Total Sampling sejumlah 60 orang. Hasil penelitian menunjukkan bahwa proses penyembuhan luka dengan khitan elektrik cauter dari hari  ke-I, III dan VII mengalami regenerasi. Dimana hari III ke Khitan dengan smart klamp regenerasi nya 90% dan Khitan dengan elektrik cauter regenerasi nya 80%, sedangkan pada hari VII sama sama regenerasinya 100%. Dengan demikian perlu disarankan agar diharapkan pelayanan kesehatan perlu menerapkan khitan dengan elektrik chauter dan smart klamp untuk mempercepat proses penyembuhan luka.